Board gender diversity and sustainability reporting quality: evidence from Malaysian companies - Nur Azah, Mohd Daud (2017)
This study examines the effect of board gender diversity on sustainability reporting quality in case of Malaysia. Many studies that investigated the relationship between board gender diversity and sustainability reporting quality were done in foreign countries. Therefore, this study contributes to the literature in this field of study in Malaysia. The theoretical foundation for this study was supported by agency theory and resources dependency theory. The main source of information for this study was obtained from the sustainability report and annual report for the fiscal year 2016. The selected samples include of Malaysian listed companies in the main board Bursa Malaysia. Final sample consists of 98 companies. By using the ordered- probit and logistic regression analysis, the results show that there is positive relationship between the number of women on boards and proportion of women directors towards sustainability reporting quality. However, with regards to the result for independent women directors show that the relationship is not statistically significant. This study can conclude that board gender diversity can influence a better quality of sustainability reporting, supporting the regulator’s initiative to promote gender diversity in the corporate boardrooms.